The Role of the Pacak Spensa Learning House through Online Learning - Salmah, Ida; Fitria, Happy; Fitriani, Yessi (Yayasan Sembilan Pemuda Indonesia, 2024)
This research aims to describe the role of the Spensa Pacak Learning House in online learning at SMP Negeri 1 Koba, Central Bangka, Bangka Belitung Islands Province. The method used in this research is a qualitative descriptive method with data collection techniques through interviews, observations, and questionnaires. The sample collection technique used a purposive sampling technique. The research results showed that the Spensa Pacak Learning House played an important role in supporting online learning at SMP Negeri 1 Koba. Most teachers and students use the Spensa Pacak site provided by the school to support the learning process. With the Spensa Pacak Learning House, online learning at SMP Negeri 1 Koba can be carried out effectively and efficiently, thus providing positive benefits for students and teachers, although there are still several obstacles in its use, such as technical problems, limited internet access and minimal role of people. old. The supporting factor is that it can be used anywhere, and for an unlimited time.